Combining fetal sonography with genetic and allele pathogenicity studies to secure a neonatal diagnosis of Bardet–Biedl syndrome - Ashkinadze, E. (2012)
Bardet–Biedl syndrome (BBS) is a rare pediatric ciliopathy characterized by marked clinical variability and extensive genetic heterogeneity. Typical diagnosis of BBS is secured at a median of 9 years of age, and sometimes well into adolescence. Here, we report a patient in whom prenatal detection of increased nuchal fold, enlarged echogenic kidneys, and polydactyly prompted us to screen the most commonly mutated genes in BBS and the phenotypically and genetically overlapping ciliopathy, Meckel–Gruber syndrome (MKS). We identified the common Met390Arg mutation in BBS1 in compound heterozygosity with a novel intronic variant of unknown significance (VUS). Testing of mRNA harvested from primary foreskin fibroblasts obtained shortly after birth revealed the VUS to induce a cryptic splice site, which in turn led to a premature termination and mRNA degradation. To our knowledge, this is the earliest diagnosis of BBS in the absence of other affected individuals in the family, and exemplifies how combining clinical assessment with genetic and timely assays of variant pathogenicity can inform clinical diagnosis and assist with patient management in the prenatal and neonatal setting.